2022
DOI: 10.1007/s13353-021-00681-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and genomic characterization followed by single-step genomic evaluation of withers height in German Warmblood horses

Abstract: Reliability of genomic predictions is influenced by the size and genetic composition of the reference population. For German Warmblood horses, compilation of a reference population has been enabled through the cooperation of five German breeding associations. In this study, preliminary data from this joint reference population were used to genetically and genomically characterize withers height and to apply single-step methodology for estimating genomic breeding values for withers height. Using data on 2113 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…A high similarity of breeds at a MS level could therefore be assumed. Combined with the rather strong connectedness between the breeds (Nolte et al 2019 ; Vosgerau et al 2022 ), an imputation of all breeds together seemed feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A high similarity of breeds at a MS level could therefore be assumed. Combined with the rather strong connectedness between the breeds (Nolte et al 2019 ; Vosgerau et al 2022 ), an imputation of all breeds together seemed feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Haberland et al (2012) observed that, for animals with a large number of progeny records available, additional gain in accuracy from GEBV is small. In the same way, in the study of Vosgerau et al (2022) about withers height, the increase in reliability was greater for animals with a small number of offspring.…”
Section: Resultsmentioning
confidence: 77%
“…The impact of genomic breeding values (GEBVs) on the accuracy of EBVs has been analysed in previous studies (Haberland et al, 2012;Vosgerau et al, 2022). Haberland et al (2012) observed that, for animals with a large number of progeny records available, additional gain in accuracy from GEBV is small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduction and behaviour traits are the least reported in the HorseQTLdb. Among the most recent studies of important Equine QTLs are; Osteochondrosis (Drabbe et al 2022), Height at Withers (Vosgerau et al 2022), and gait and racing performance (Ricard and Duluard 2022). The difficulties in recording behaviour phenotypes probably reflect the small number of genetic associations reported in both OMIA and HorseQTLdb.…”
Section: Important Monogenic and Multifactorial Diseases And Traits I...mentioning
confidence: 99%